Efeito da relação proteína degradável no rúmen: proteína indegradável no rúmen e do tipo de volumoso na dieta de ruminantes - Hoffmann, Fabiane (2020)
The objective of this study was to evaluate the effect of the combination of two sources of forage and two ratio rumen degradable protein in the rumen (RDP) and rumen undegradable protein (RDP:RUP) on intake, digestibility, ruminal parameters and microbial protein synthesis in cattle. Four castrated males, Jersey-breed, cannulated in the rumen with an average live weight of 315 Kg1 were used in a 4x4 Latin square experimental design, with four treatments in a 2x2 factorial arrangement. The treatments were, ABR= ryegrass as a source of forage with low RDP:RUP ratio (RDP= 60% of CP); AAR= ryegrass as a source of forage with high RDP:RUP ratio (RDP= 65% of CP); TBR= tifton as a source of forage with low RDP:RUP and TAR= tifton ratio as a forage source with high RDP:RUP ratio. Animals fed tifton hay showed higher intake of dry matter, organic matter and consumption of soluble carbohydrates . The different RDP:RUP ratios did not influence the variables of consumption and digestibility. Ammonia and amino acid concentrations were higher in cattle fed tifton hay. The high RDP:RUP ratio promoted higher concentrations of sugars, while the low RDP:RUP ratio promoted higher ammonia concentration in ruminal fluid. There was interaction between forage and the RDP:RUP ratio for pH and amino acids. More important than the type of forage provided is the quality of this feedd, observing the bromatological composition and proven by higher consumption, it is verified that tifton hay was higher in relation to ryegrass hay. The RDP:RUP ratios used were not determinant in any of the results found and for this reason concluded that both RDP:RUP ratios can be used in tropical or temperate grass diets.